La constitucionalización del derecho procesal y su repercusión en la reforma de la normatividad ritual (CPP) y el sistema de justicia penal - Rodríguez Hurtado, Mario Pablo (2013)
This article examines the close relationship between criminal procedure and constitutional law within a democratic State framework as well as the guarantees provided from a constitutional point of view in accordance with the current context of human rights globalization. Then, the author approaches us to criminal procedure main principles and guarantees, procedural models historically formed. Finally, it presents an interesting Criminal Procedural Code analysis describing guarantees, principles and procedural models recognized in our country.